Effect of international activity on firm performance - Joachim Wagner (IZA World of Labor, 2019)
There is evidence that better performing firms tend to enter international markets. Internationally active firms are larger, more productive, and pay higher wages than other firms in the same industry. Positive performance effects of engaging in international activity are found especially in firms from less advanced economies that interact with partners from more advanced economies. Lowering barriers to the international division of labor should therefore be part of any pro-growth policy.
Keywords: F16; 330; firms; trade; offshoring; productivity; employment; wages; survival